Plasma Nutfah Jagung sebagai Sumber Gen dalam Program Pemuliaan - Sri Gajatri Budiarti (Buletin Plasma Nutfah, 2007)
In December 2005, maize germplasm collection at the institute were 886 accessions consisted of 581 local varieties, 165 introduced varieties, 107 inbred, lines, and 33 old and the present improved varieties. Required traits in varietal improvement or development are drought tolerant, tolerant to Al-toxicity, early maturity, have better quality, resistant to downy mildew disease, resistant to insect Atherigona exigua and high yield. Maize germplasm must be characterized accordingly. Evaluation for Al toxicity was conducted at Tamanbogo, Lampung, 100-200 accessions of maize germplasm and tolerance to drought were conducted in Jakenan and Imogiri Central Java, 63-100 accessions. Evaluation for downy mildew resistance was conducted at Cikeumeuh Bogor, 100-200 accessions. Evaluation for resistance to seedingfly was conducted at Cikeumeuh, 75-100 accessions. The results of evaluation conducted from 1999-2004 were: 30 accessions tolerant to drought, 21 accessions. tolerant to Al-toxicity, 70 accessions resistant to downy mildew disease (Peronosclerospora maydis), 22 accessions resistant to seeding fly (Atherigona exigua), 126 accessions had very early maturity <80 days (consisted of 31 accessions had yellow seed, 35 accessions had white seed, and 60 accessions had other colour seed). Accessions having good characters, need to be further tested prior to their use in the breeding program, particularly the accessions resistant to Atherigona exigua in monoculture test. AbstrakSampai Desember 2005 koleksi plasma nutfah jagung di bank gen BB-Biogen berjumlah 886 aksesi yang terdiri dari 581 varietas lokal, 165 varietas introduksi, 107 galur inbrida, dan 33 varietas unggul lama dan baru. Sifat-sifat yang diinginkan dalam perakitan varietas antara lain adalah toleran kekeringan dan keracunan Al, berumur genjah, mutu gizi baik, dan tahan terhadap penyakit bulai, hama lalat bibit, dan hasil tinggi. Untuk tujuan tersebut, plasma nutfah perlu dikarakterisasi dan dievaluasi. Uji toleransi keracunan Al dilakukan di Tamanbogo, Lampung terhadap 100-200 aksesi. Uji kekeringan dilakukan di Jakenan dan Imogiri, Jawa Tengah terhadap 63-100 aksesi. Uji ketahanan penyakit bulai dilakukan di Cikeumeuh, Bogor terhadap 100-200 aksesi. Pengujian ketahanan terhadap lalat bibit dilakukan di Cikeumeuh terhadap 75-100 aksesi. Hasil pengujian sejak tahun 1999-2007 diperoleh informasi sebagai berikut: sebanyak 30 aksesi mempunyai sifat toleran terhadap kekeringan, 21 aksesi toleran keracunan Al, 70 aksesi sangat tahan penyakit bulai (Peronosclerospora maydis), dan 22 aksesi tahan terhadap hama lalat bibit (Atherigona exigua), 126 aksesi berumur sangat genjah (<80 hari). Aksesi-aksesi tersebut perlu diuji kembali kemantapan sifatnya sebelum digunakan dalam program pemuliaan, khususnya untuk aksesi yang tahan hama lalat bibit perlu diuji secara monokultur.